23 RIGHT ATRIAL AND RIGHT VENTRICULAR THROMBI WITH SEPSIS AND PULMONARY EMBOLI. Issue 1 (1st January 2007) - Douglas, C. J.; Quin, E. M.; Winscott, J. G.; Skelton, T. N.
Abstract : A male 34-year-old hypertensive smoker with hypertension, hepatitis C, and a history of multiple drug abuse presented to the emergency department with malaise, fever, and chills for approximately 1 week. Physical examination revealed a systolic ejection murmur heard throughout the precordium. Labwork showed leukocytosis, mild normocytic anemia, and thrombocytosis. Radiography revealed mild cardiomegaly and a left pleural effusion as well as a 2 cm nodule in the right midlung and a 2 × 5 cm mass in the left lower lobe. He was admitted and started on empiric antibiotic therapy. Initial blood cultures returned Staphylococcus epidermidis and Acinetobacter baumannii . Computed tomography of the chest was performed to evaluate the pulmonary masses and showed multiple peripheral masses in both lungs; also noted was a right atrial mass. Echocardiography was performed to better characterize the atrial mass and demonstrated a mass in the right atrium measuring 2.6 × 3.9 cm as well as a mass along the posterior wall of the right ventricle measuring 1.3 × 1.4 cm with severe left ventricular systolic dysfunction. Echocardiography-guided biopsy of the right atrial mass was consistent with thrombus. Anticoagulation was initiated with enoxaparin and warfarin. He was discharged home after 3 weeks of antibiotic therapy on warfarin, carvedilol, lisinopril, and intravenous vancomycin and levofloxacin with plans to continue intravenous antibiotics for a total of 6 weeks. Two weeks following discharge, he was seen in follow-up and had repeat blood cultures, which were sterile. Six weeks following discharge, a repeat echocardiogram showed mild left ventricular systolic dysfunction with an ejection fraction of 45%; there was no indication of a mass or thrombus in either the right atrium or right ventricle. Intracardiac masses are uncommon, occurring in less than 0.1% of autopsies. The differential diagnosis of these masses is broad and includes myxomas, papillary fibroelastomas, lipomatous hypertrophy of the atrial septum, thrombi, and malignancies (either primary or metastatic). Although left ventricular thrombi are commonly noted, particularly with severe left ventricular systolic dysfunction and following myocardial infarction, and right atrial thrombi are often noted (particularly in the presence of pulmonary embolism), right ventricular thrombi are exceedingly rare. To our knowledge, this is the first case report of what we assume to be right ventricular thrombus in situ related to sepsis.